The Use of Chain Spelling Game to Improve Students’ Vocabulary Mastery at The 7th Grade of SMP Muhammadiyah Ajakkang - Aulia, Shela; Mia, Nurul Aini Islamiah; Ardiana (IKIP Siliwangi, 2025)
This study investigates the effectiveness of the chain spelling game in improving vocabulary skills among 7th-grade students at SMP Muhammadiyah Ajakkang and evaluates their perceptions of its effectiveness. A pre-experimental design was employed with a sample of 11 students selected through total sampling. The primary instrument for data collection was a vocabulary test, and the data were analyzed using SPSS version 27. The results indicated a significant improvement in the average vocabulary score from the pre-test (39.54) to the post-test (65.45). -7.42, with 10 degrees of freedom (df), and the p-value is less than 0.001 (p < 0.001), confirming that the chain spelling game positively impacted students’ vocabulary mastery. The paired sample t-test analysis showed a mean score difference of 33.68, reflecting a substantial improvement in students' scores after the intervention. The standard deviation of (11.57) and the standard error of the mean (3,49) indicate individual differences and the reliability of the results. The 95% confidence interval for the mean difference ranged from (39.54) to (65.45), suggesting the improvement is statistically significant. In conclusion, the chain spelling game proved to be an effective and engaging tool for enhancing vocabulary skills, providing an interactive and enjoyable method for improving students’ language proficiency.